An administrative perspective of Tokyo (TMG, 1977)
Tokyo, the capital of Japan, has a history of more than five hundred years, dating from 1457 when a local warrior named Ota Dokan built his castle in a deserted village called Edo. The books will give general information on the administration of Tokyo will prove helful in explaining the actual state of affairs in japan's largest metropolis.